2019
DOI: 10.1088/1757-899x/563/4/042068
|View full text |Cite
|
Sign up to set email alerts
|

Design and experimental performances of a piezoelectric stick-slip actuator for rotary motion

Abstract: In order to reduce the regression phenomenon of the piezoelectric stick-slip actuator, and improve the output performance, a piezoelectric stick-slip actuator with regular octagonal flexible hinge mechanism is proposed in this paper. The pseudo-rigid body method is used to analyze the regular octagonal flexible hinge mechanism and the flexible driving foot respectively.A prototype is fabricated to test the working performance and the results demonstrate that the minimum step is 0.01μm, the maximum speed is 145… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Taking a simple FHMs-PSSA as the research object, Shao et al (2019b) stated that the step displacement mainly depended on the excitation signal’s voltage and the friction between the stator and the rotor. As shown in Figure 7(f), Ding et al (2019) designed a rotary FHMs-PSSA with a regular octagonal mechanism to suppress the backward motion; through the cooperation of four compliant feet in the driving process, the static friction in the stick phase could be increased, and the dynamic friction in the slip phase could be reduced. However, the above-mentioned rotary actuators all adopted bearings to change from translational motion to rotational motion, and the nonlinear trend of displacement curve in the step process caused by the gap between bearings was inevitable (Huang et al, 2016); to avoid the error, Le et al (2019) and Wang et al (2020a) proposed FHMs-PSSAs with self-centering function based on flexure hinge structure, as shown in Figure 7(g).…”
Section: Progress In Structural Design Of Fhms-pssasmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking a simple FHMs-PSSA as the research object, Shao et al (2019b) stated that the step displacement mainly depended on the excitation signal’s voltage and the friction between the stator and the rotor. As shown in Figure 7(f), Ding et al (2019) designed a rotary FHMs-PSSA with a regular octagonal mechanism to suppress the backward motion; through the cooperation of four compliant feet in the driving process, the static friction in the stick phase could be increased, and the dynamic friction in the slip phase could be reduced. However, the above-mentioned rotary actuators all adopted bearings to change from translational motion to rotational motion, and the nonlinear trend of displacement curve in the step process caused by the gap between bearings was inevitable (Huang et al, 2016); to avoid the error, Le et al (2019) and Wang et al (2020a) proposed FHMs-PSSAs with self-centering function based on flexure hinge structure, as shown in Figure 7(g).…”
Section: Progress In Structural Design Of Fhms-pssasmentioning
confidence: 99%
“…Non-resonant type rotary FHMs-PSSAs: (a) the bridge type rotary FHMs-PSSA (Li et al, 2015b); (b) the double rectangular trajectories driving type FHMs-PSSA (Wang et al, 2018); (c) variable force couple driving type FHMs-PSSA (Wang et al, 2017b); (d) the FHMs-PSSA with centipede foot bionics (Wang et al, 2017a); (e) the FHMs-PSSA with a constant contact status (Liu et al, 2019a); (f) the FHMs-PSSA with regular octagonal mechanism (Ding et al, 2019); and (g) the FHMs-PSSA with self-centering function by Wang et al (2020a). Resonance type rotary FHMs-PSSAs: (h) the FHMs-PSSA with asymmetric stator proposed by Pan et al (2019); and (i) the FHMs-PSSA based on a symmetric triangular mechanism proposed by Zhang et al (2019b).…”
Section: Progress In Structural Design Of Fhms-pssasmentioning
confidence: 99%
See 1 more Smart Citation
“…realize smooth motion). For example, in structural innovation, a piezoelectric stick-slip rotary actuator with regular octagonal flexure hinge mechanism was designed by Ding et al (2019), and the coupling of four driving feet was used to suppress the backward motion. Qin et al (2019aQin et al ( , 2019b proposed a flexure hinge drive mechanism, which realized active control of contact force through two piezoelectric stacks, thus suppressing backward motion; in their other studies, they also found that piezoelectric actuators had better output smoothness at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that most of the previously developed stickslip piezoelectric actuators are designed to achieve the linear motion [18][19][20][21][22][23][24], and the design of rotary actuators is relatively less reported. Currently, only a few studies focused on the rotary actuators [25][26][27]. For example, Li et al [25] designed a stick-slip piezoelectric rotary actuator by using a bridge-type flexure hinge mechanism.…”
Section: Introductionmentioning
confidence: 99%